Pengaruh rasio kinerja keuangan pada harga saham perusahaan prospektus - Akadiati, Victoria Ari Palma; Suhendi, Andres; Jatiningrum, Citrawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
The purpose of this study is to analyze whether there is an influence on the ratio of financial performance to stock prices. Financial performance ratios are proxied using Return on Assets, Debt to Equity Ratio, Earnings Per Share, Price Earning Ratio and stock prices are proxied using Price to Book Value. This type of quantitative research uses multiple linear regression data analysis techniques and secondary data with a sample of prospectus companies that conducted initial public sales on the stock market or IPO in 2021. The results showed that Return on Asset (ROA) and Price Earning Ratio (PER) have a significant influence on stock prices. The implication of this study is that prospectus companies that conduct an initial public offering or IPO can further increase the factors that affect the Return on Asset ratio in generating profits and maintaining the effectiveness of the company's operational activities in order to increase the company's return on investment. The difference with other studies is that research is conducted on companies that have just sold their shares for the first time so that investors can consider choosing shares of prospectus 2021 companies by paying attention to the level of financial performance ratio.